The Effect of Mindfulness Training on Distress Tolerance in Art Students at Islamic Azad University, Central Tehran Branch - Mohammad Ali Beigi, Ziba; Haghighat, Sara (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of mindfulness training on distress tolerance among art students at Islamic Azad University, Central Tehran Branch.Methods and Materials: The present study employed a quasi-experimental design with a pretest–posttest structure and a control group. The statistical population consisted of all art students at Islamic Azad University, Central Tehran Branch, during the 2026 academic year. The research sample included 30 students selected through purposive sampling and randomly assigned into an experimental group (n = 15) and a control group (n = 15). Data were collected using the Distress Tolerance Scale developed by Simmons and Gaher (2005), which measures tolerance, absorption, appraisal, and regulation components of distress tolerance. The experimental group participated in a 10-session mindfulness training program, while the control group received no intervention. Data were analyzed using multivariate analysis of covariance (MANCOVA) with IBM SPSS software.Findings: The results of the multivariate analysis of covariance demonstrated that mindfulness training significantly improved distress tolerance and its components among students in the experimental group compared with the control group. Significant differences were observed between the two groups in tolerance (F = 6.348, p < .01), absorption (F = 5.995, p < .01), appraisal (F = 4.275, p < .01), regulation (F = 3.430, p < .01), and total distress tolerance (F = 2.540, p < .01). The overall group effect was also statistically significant (F = 6.578, p < .01), indicating that mindfulness training effectively enhanced students’ capacity to tolerate and regulate emotional distress.Conclusion: The findings suggest that mindfulness training plays a significant role in improving distress tolerance among university students by enhancing emotional awareness, cognitive appraisal, emotional regulation, and adaptive coping abilities. Therefore, mindfulness-based interventions may serve as effective psychological approaches for promoting emotional resilience and psychological well-being among art students and other student populations experiencing emotional and academic stress.